2020
DOI: 10.21203/rs.3.rs-16122/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disinfectant Wipes Transfer Clostridioides difficile Spores from Contaminated Surfaces to Uncontaminated Surfaces during the Disinfection Process

Abstract: Background: Pre-wetted disinfectant wipes are increasingly being used in healthcare facilities to help address the risk of healthcare associated infections (HAI). However, HAIs are still a major problem in the US with Clostridioides difficile being the most common cause, leading to approximately 12,800 deaths annually in the US. An underexplored risk when using disinfectant wipes is that they may cross-contaminate uncontaminated surfaces during the wiping process. The objective of this study was to determine t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In clinical practice it will be relevant to avoid that the wiping itself contributes to the spread of the C. difficile spores on the treated surfaces [19]. That is why the results from test fields 2 to 4 have relevant practical implications.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice it will be relevant to avoid that the wiping itself contributes to the spread of the C. difficile spores on the treated surfaces [19]. That is why the results from test fields 2 to 4 have relevant practical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Nkemngong and colleagues showed that cleaning cloths quickly become contaminated and spread MDRO from contaminated areas to non-contaminated areas. 2 Previous studies have shown that terminal cleaning fails to remove bacteria from surfaces, especially the bed. 3,4 It is interesting that the authors did not describe a different procedure for cleaning the mattress.…”
mentioning
confidence: 99%